“Haptically Mediated” radio listening and its commodification: the remediation of radio through digital mobile devices - Gazi, Angeliki; Bonini, Tiziano (My University, 2018)
This article aims to rediscover the tactile aspects of radio listening, which until now have been underestimated by radio scholars, and to describe how haptic radio listening has evolved, from the beginning of broadcasting to the arrival of digital media. This article will first perform an overview of the studies that have dealt with the haptic dimension of media, then focus on what we call "haptically mediated" radio listening, a specific form of listening made possible by the interaction with radio content through mobile digital devices, and conclude with a critical depiction of the implications of haptically mediated listening for audience commodification.
Keywords: Life; Internet; Labor; Audience commodity; Informational capitalism